A patient with appendicitis acuta? - Stępińska, Katarzyna (Journal of Education, Health and Sport, 2022)
Acute appendicitis has always been correlated with a short patient’s medical history and a sudden onset of symptoms. Nevertheless, in some patients the duration of the symptoms is prolonged, up to several days. The following case illustrates this course of the disease.